Rancang Bangun Insinerator Pengolahan Sampah dengan Penerapan Teknologi Termal yang Ramah Lingkungan - Estu Broto, Prasepvianto; Fitriyanti; Amirin Kusmiran; Khaerul Ihsan (JFT : Jurnal Fisika dan Terapannya, 2024)
Concerns about environmental problems such as increasing the volume of waste which if not treated properly will affect environmental pollution which can damage soil fertility and also have an impact on human health. This study aims to make a waste processing incinerator with the application of thermal technology. Oil and water stoves are used as media for burning waste, the stove will burn the waste that has been put into the combustion chamber made of drums coated with clay. This clay coating aims to increase the temperature of the combustion chamber so that maximum combustion is obtained with minimal smoke. From the waste burning test, the temperature measurement results in the combustion chamber reached 751ºC. Carbon gas measured at the maximum temperature around the incinerator is 27 ppm. From the data obtained, it can be concluded that waste burning with an incinerator has been made to minimize air pollution so that it can be used for solutions in environmentally friendly waste processing.